A Study of Variation of Nutrient Foramen of Dry Adult Humerus - Poudel, Abhishek; Satyal, Biswas (Journal of Nepalgunj Medical College, 2019)
Introduction: Nutrient artery is the chief artery for the blood supply of the long bone and passes through the nutrient foremen which lie towards the medial border in the anteromedial surface below the midpoint in humerus. During the surgical procedures like bone grafting and microsurgical vascularized bone transplantation, the knowledge of nutrient foramen is important. The nutrient artery plays an important role in nonunion and delayed union of fracture bone. Aims and Objectives: The aim of this study is to determine the number, position and direction of the nutrient foramina of humerus. Materials and Methods: 50 humerus, 21 of right and 29 of left side were studied without any pathological disorders. Results: Single nutrient foremen was observed in 80% humerus. Double foramen in 16%. There was no foramen in 4% humerus. It was also concluded that 88% humerus had the nutrient foremen in anteromedial surface. Nutrient foremen were dominant in Zone II with 82%. All foramen were directed towards the lower end of humeri. Conclusion: The presence of single foramen in the zone II was dominant. The nutrient foramina were also dominant in the anteromedial surface of the humerus.